Nano marine traditional Chinese medicine composite dressing, preparation method thereof and application of nano marine traditional Chinese medicine composite dressing in rapid hemostasis and wound repairing medicine
Nanomarine Chinese medicine composite dressing was prepared by ultrasonic sand grinding technology, and nano-marine Chinese medicine composite dressing was prepared through cross-linking of sodium alginate and calcium citrate, which solved the problem of dissolution of active ingredients of scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered scattered sca and hemostasis effect, achieving rapid healing of wounds.
Patent Information
- Application Number
- CN202411556091.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, the active ingredients of the squid can easily dissolve during nano-grinding, resulting in low bioavailability of the drug and difficult to effectively improve the hemostatic effect of the drug.
Nanomarine Chinese medicine composite dressing is prepared by ultrasonic sand grinding technology to improve the solubility and bioavailability of the drug.
The active ingredient retention of squid is achieved, the bioavailability and hemostatic effect of the drug are improved, and the hydrogel has good biocompatibility and biodegradability, which promotes rapid wound healing.
Smart Images

Figure CN119386257A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of marine biological material application, and specifically relates to a composite dressing of nano marine traditional Chinese medicine-cuttlebone combined with sodium alginate, etc., which can quickly stop bleeding and repair wounds, and a preparation method thereof. Background Art
[0002] The skin is the largest organ in the human body and has important barrier and protective functions. Therefore, it is also a part that is prone to damage. In China, about 100 million patients need wound care every year, of which about 30 million patients have severe skin trauma. This is not only a personal burden, but also has a great impact on families and the social medical system. Whether it is an acute wound or a chronic wound, wound healing is a complex, strictly regulated and important physiological process that maintains the integrity of the skin. It is crucial to maintain the barrier function of the skin and protect all skin functions. Therefore, how to effectively treat skin injuries while avoiding delayed healing or even non-healing caused by various reactions during the treatment process has always been one of the difficult problems that plague the biomedical community.
[0003] Traditional Chinese medicine has a long history of research on wound healing. It has a good promoting effect, has little toxicity and side effects, and can be used according to the different causes of the wound. The sea cucumber sheath, also known as the cuttlefish bone, is a marine animal needleless cuttlefish ( Sepiella Main Drum of Rechelbrune )、Golden Squid( Sepia esculenta Hoyle ) has the effects of astringent hemostasis, acid relieving and analgesia, moisture absorption and sore astringence. It is used as a hemostatic drug in traditional Chinese medicine. Modern research has found that it also has the effects of epidermal repair, antibacterial and wound healing. When the sea cucumber sheath is used externally, it is usually ground into powder and applied to the affected area. Although the surface area is large after crushing and it is easy to disperse, the chemical properties of the powder are not very stable and it is easy to deteriorate. The production process and storage method require strict requirements. Polyvinyl alcohol (PVA) is a hydrophilic material that forms a network structure during the freeze-thaw-thaw process, giving it properties such as stretchability, ductility, and conformability. The single internal network structure will lead to poor mechanical properties, poor toughness, and poor recyclability of PVA hydrogels, which seriously limits its application. Introducing a new network structure is one of the most effective ways to enhance the mechanical strength of PVA. Sodium alginate (SA) comes from marine plants. It is a natural hydrophilic polysaccharide with high biocompatibility and good degradability. It is stable and non-toxic, and its immunogenicity is lower than that of natural macromolecules from animal sources. There are a large number of carboxylate (-COO-) groups distributed in the molecular chain. 2+ The coordination and cross-linking with -COO- forms alginate hydrogel, which is used as a drug sustained-release carrier.
[0004] The delivery of poorly soluble drugs has always been an important part of the pharmaceutical preparation field. According to studies, more than 40% of potential drugs are limited in drug development due to poor solubility. Poorly soluble drugs usually show low bioavailability. With the advancement of various solubilization and particle size reduction technologies, the problem of poorly soluble drug delivery may be solved, and more drugs can be obtained through emerging technology research. Cuttlebone, as a traditional mineral marine Chinese medicine, has the effects of astringent hemostasis, astringent semen and leukorrhea, acid relieving pain, and moisture astringent. It can be used externally to treat injury bleeding, eczema and wet sores, and ulcers that do not heal. "Compendium of Materia Medica" records that "grind it into powder and apply it to children's rickets, smelly pox sores, men's genital sores, hot and fire injuries, and bleeding from falls." Nanotechnology can increase the specific surface area and active sites of cuttlebone, which can effectively improve the solubility and bioavailability of drugs, and improve the dispersion and uniformity of drugs in preparations. Hydrogel is a three-dimensional hydrophilic polymer network with a structure similar to that of the extracellular matrix. It has good biocompatibility and can reduce the risk of wound infection by absorbing wound exudate and maintaining a moist environment, providing good potential for promoting the repair of damaged tissue.
[0005] A Chinese patent (CN202410221843.8) discloses a polysaccharide coating liquid and a preparation method thereof. Neutral polysaccharides are prepared into a solution using slightly acidic electrolyzed water. Combined with the solution nano-grinding treatment, a polysaccharide coating liquid with excellent antibacterial properties and uniform and stable dispersion of polysaccharide components is prepared. The nano-grinding is carried out in the range of 25-30°C and the rotation speed is 800-900rpm; however, nano-grinding at this temperature is very likely to cause the effective ingredients of the cuttlebone to dissolve, resulting in a large loss.
[0006] A Chinese patent (CN202211476089.X) discloses a hemostatic hydrogel and its preparation method and application. A hydrophilic polymer containing an aldehyde group or a hydrophilic polymer with an aldehyde group in the polymer group through an oxidation reaction is used, and oxidized sodium alginate is used as one of the raw materials for preparing the hydrogel. A polymer containing an amino group or a polymer modified by aminoation is used as another raw material for preparing the hydrogel, and cuttlebone powder is evenly dispersed in the polymer solution containing the amino group. The swelling performance tends to saturation in about one hour. The cuttlebone powder of this technical solution is 100 mesh-500 mesh, and the temperature resistance of the oxidized sodium alginate is 80°C. Exceeding this temperature will cause it to lose stability and thickening effect.
[0007] A Chinese patent (CN202211068097.0) discloses a cuttlebone electrospun nanofiber hemostatic dressing that can quickly stop bleeding and a method for making the same. The commercially available cuttlebone is initially crushed with a high-speed grinder, and the cuttlebone coarse powder is then deproteinized and decolorized. The dried cuttlebone powder is ground with an agate mortar to a particle size of 3-8 microns. The deproteinization and decolorization adopted in this technical solution require alkali treatment and heating to 100°C and stirring, which can easily cause the loss of polysaccharides (chitin) in the cuttlebone. Summary of the invention
[0008] In view of the above problems, the present invention aims to provide a nano marine traditional Chinese medicine composite dressing to solve the problem of low bioavailability and improve the hemostatic effect of the drug.
[0009] To achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for preparing a nano marine traditional Chinese medicine composite dressing, comprising the following steps: Step 1, grinding the cuttlebone (decoction pieces) and passing through a (80 mesh) sieve to obtain cuttlebone powder; then ultrasonically grinding (using an ultrasonic sand mill) to a particle size of 1nm-200nm to obtain nano-cuttlebone, and drying (blast drying or freeze drying, wherein the blast drying temperature is 55-65°C) and sterilizing (ultraviolet sterilization, the sterilization time is 0.5-2h); Step 2, dissolving a certain amount of sodium alginate, adding a certain amount of the nano-cuttlebone obtained in step 1 and calcium citrate, so that the carboxyl group in the sodium alginate is cross-linked with the calcium ion; adding the obtained nano-cuttlebone solution to the hydrophilic polymer solution, and adding a certain amount of acrylic acid, potassium persulfate and glycerol, heating in a water bath at 80-90° C. for 4-6 hours to obtain a hydrogel sample; Step 3, soaking the obtained hydrogel sample in water for 20-30 hours to remove the acrylic acid or hydrophilic polymer that is not cross-linked on the surface.
[0010] Preferably, the ultrasonic sand milling process in step 1 is wet grinding, the medium is water, and the ratio of cuttlebone powder to water is 1: (10-20).
[0011] Preferably, in the ultrasonic sand milling process in step 1, the amount of zirconium beads added is 80-90wt% of the cuttlebone powder, and the diameter of the zirconium beads is 0.3-0.4mm.
[0012] Preferably, in step 1, sodium hexametaphosphate (defoaming agent, dispersant) is added in an amount of 0.3 wt % of the cuttlebone powder during the ultrasonic sand milling process.
[0013] Preferably, the rotation speed in the ultrasonic sand milling process in step 1 is 3000 r / min.
[0014] Preferably, in the ultrasonic sand milling process in step 1, circulating condensed water is used to control the temperature below 8°C to prevent the machine and materials from being heated.
[0015] Preferably, the hydrophilic polymer in step 2 is at least one of polyvinyl alcohol, polyethylene glycol and gelatin, and the mass concentration of the hydrophilic polymer solution is 6-14%.
[0016] Preferably, the mass concentrations of sodium alginate, nano-cuttlebone and calcium citrate used in the nano-cuttlebone solution in step 2 are 1-2%, 1-3% and 0.1-0.2%, respectively.
[0017] Preferably, the volume ratio of the nano-cuttlebone solution to the hydrophilic polymer solution in step 2 is 1:0.8-1.2.
[0018] Preferably, the amounts of acrylic acid, potassium persulfate and glycerol used in step 2 are 6-14%, 0.25-0.6% and 0.6-1.4% of the total weight of the two solutions, respectively.
[0019] The beneficial effects of the present invention are: (1) The present invention uses ultrasonic sand milling technology to nano-crush sea cucumbers, which is ground at low temperature to reduce the dissolution of active ingredients of drugs. Processing marine mineral Chinese medicines into nano-powders can increase their specific surface area and active sites, effectively improve the solubility, bioavailability and efficacy of drugs, and improve the dispersibility and uniformity of drugs in preparations.
[0020] (2) The present invention prepares nano-cuttlebone hydrogel by combining polyvinyl alcohol and sodium alginate through a cyclic freeze-thaw method. The hydrogel has excellent properties such as hydrophilicity, good biocompatibility and biodegradability, can provide a microenvironment for moist healing, and blocks direct contact between the wound surface and the outside world, and has good hemostatic and healing-promoting abilities. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The present invention is a schematic diagram of the preparation process of the nano-cuttlebone and the dressing.
[0022] Figure 2 The scanning electron microscope images and particle size distribution of cuttlebone powders with different particle sizes according to the embodiments of the present invention are shown.
[0023] Figure 3 The antibacterial properties of 3-8 micron cuttlebone and nano-cuttlebone hydrogels according to the embodiments of the present invention.
[0024] Figure 4 The cytotoxicity of 3-8 micron cuttlebone and nano-cuttlebone hydrogel according to the embodiment of the present invention.
[0025] Figure 5This is a scanning electron micrograph of 3-8 micron cuttlebone and nano-cuttlebone hydrogel according to an embodiment of the present invention.
[0026] Figure 6 The present invention shows the tensile properties of the nano-cuttlebone hydrogel.
[0027] Figure 7 The present invention shows the swelling performance of the nano-cuttlebone hydrogel according to the embodiment of the present invention.
[0028] Figure 8 Schematic diagram of a mouse liver hemostasis experiment using a nano-cuttlebone hydrogel dressing according to an embodiment of the present invention.
[0029] Fig. 9 This is a schematic diagram of an animal experiment on wound healing using a nano-cuttlebone hydrogel dressing according to an embodiment of the present invention. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The specific embodiments described herein are only used to explain the relevant content, rather than to limit the present disclosure. Without departing from the present invention, modifications or replacements made to the method, steps or conditions of the present invention all belong to the scope of the present invention. For ease of description, only the parts related to the present disclosure are shown in the accompanying drawings.
[0031] It should be noted that, in the absence of conflict, the embodiments of the present disclosure and the features in the embodiments may be combined with each other. The present disclosure will be described in detail below in conjunction with the accompanying drawings and the embodiments.
[0032] Several examples of preparation methods of nano-cuttlebone and its wound dressing are given below, and representative hydrogels are selected for performance analysis.
[0033] Example 1 A method for preparing nano-cuttlebone comprises the following steps: Step 1, grind the cuttlebone slices with a universal grinder and pass through an 80-mesh sieve to obtain cuttlebone 80-mesh powder for later use; Step 2, grind the 80-mesh cuttlebone powder by an ultrasonic sand mill, keep the slurry added each time at 3-5 L, the mass-liquid ratio is 1:10, select 0.3-0.4 mm zirconium beads, add 85%, add 0.3% sodium hexametaphosphate for defoaming, start circulating water condensation, and grind until the particle size of the cuttlebone reaches nanometer level; Step 3, filtering the nano-cuttlebone slurry, washing with deionized water until the pH is neutral (to remove the sodium hexametaphosphate), and then air-drying or freeze-drying to obtain nano-powder, wherein the air-drying temperature is 60° C.; Step 4: Put the dried nano-cuttlebone into a plastic film bag and sterilize it with ultraviolet light for 1 hour. After sterilization, set it aside.
[0034] Example 2 A method for preparing nano-cuttlebone comprises the following steps: Step 1, grind the cuttlebone slices with a universal grinder and pass through an 80-mesh sieve to obtain cuttlebone 80-mesh powder for later use; Step 2, grind the 80-mesh cuttlebone powder by an ultrasonic sand mill, keep the slurry added each time at 3-5 L, the mass-liquid ratio is 1:15, select 0.3-0.4 mm zirconium beads, add 85%, add 0.3% sodium hexametaphosphate for defoaming, start circulating water condensation, and grind until the particle size of the cuttlebone reaches nanometer level; Step 3, filtering the nano-cuttlebone slurry, washing with deionized water until the pH is neutral (to remove the sodium hexametaphosphate), and then air-drying or freeze-drying to obtain nano-powder, wherein the air-drying temperature is 60° C.; Step 4: Put the dried nano-cuttlebone into a plastic film bag and sterilize it with ultraviolet light for 1 hour. After sterilization, collect and store it.
[0035] Example 3 A method for preparing nano-cuttlebone comprises the following steps: Step 1, grind the cuttlebone slices with a universal grinder and pass through an 80-mesh sieve to obtain cuttlebone 80-mesh powder for later use; Step 2, grind the 80-mesh cuttlebone powder by an ultrasonic sand mill, keep the slurry added each time at 3-5 L, the mass-liquid ratio is 1:20, select 0.3-0.4 mm zirconium beads, add 85%, add 0.3% sodium hexametaphosphate for defoaming, start circulating water condensation, and grind until the particle size of the cuttlebone reaches nanometer level; Step 3, filtering the nano-cuttlebone slurry, washing with deionized water until the pH is neutral (to remove the sodium hexametaphosphate), and then air-drying or freeze-drying to obtain nano-powder, wherein the air-drying temperature is 60° C.; Step 4: Put the dried nano-cuttlebone into a plastic film bag and sterilize it with ultraviolet light for 1 hour. Collect it after sterilization.
[0036] Example 4 A method for preparing a nano marine traditional Chinese medicine composite dressing comprises the following steps: Step 1, dissolving sodium alginate in water to a concentration of 1wt%, adding 1wt% nano-cuttlebone, and adding 0.1wt% calcium citrate to react with sodium alginate to generate calcium ion cross-linking to obtain a solution; Step 2, adding the above solution to a 6wt% PVA aqueous solution, and adding monomer acrylic acid, adding a certain amount of initiator potassium persulfate and cross-linking agent glycerol, heating in a water bath at 85°C for 5h, and taking out the sample; the amount of acrylic acid, potassium persulfate and glycerol is 10%, 0.4% and 1% of the total weight of the two solutions respectively; Step 3: Soak the hydrogel sample in deionized water for 24 hours to remove uncross-linked acrylic acid or polymer on the surface of the hydrogel.
[0037] Step 4: sterilize the hydrogel under ultraviolet light for more than 30 minutes after demolding, and store it in a sealed container for future use.
[0038] Example 5 A method for preparing a nano marine traditional Chinese medicine composite dressing comprises the following steps: Step 1, dissolving sodium alginate in water to a concentration of 1wt%, then adding 1wt% of nano-cuttlebone, and adding 0.1% of calcium citrate to react with sodium alginate to generate calcium ion cross-linking to obtain a solution; Step 2, adding the above solution to an 8wt% PVA aqueous solution, and adding monomer acrylic acid, adding a certain amount of initiator potassium persulfate and cross-linking agent glycerol, heating in a water bath at 85°C for 5h, and taking out the sample; the amount of acrylic acid, potassium persulfate and glycerol is 10%, 0.4% and 1% of the total weight of the two solutions respectively; Step 3, soaking the above hydrogel sample in deionized water for 24 hours to remove uncross-linked acrylic acid or polymer on the surface of the hydrogel; Step 4: sterilize the hydrogel under ultraviolet light for more than 30 minutes after demolding, and store it in a sealed container for future use.
[0039] Example 6 A method for preparing a nano marine traditional Chinese medicine composite dressing comprises the following steps: Step 1, dissolving 1% sodium alginate in water, adding 1% nano-cuttlebone, and adding 0.1% calcium citrate to react with the sodium alginate with calcium ions to obtain a solution; Step 2, adding the above solution to a 10wt% PVA aqueous solution, adding an appropriate amount of monomer acrylic acid, adding a certain amount of initiator potassium persulfate and cross-linking agent glycerol, heating in a water bath at 85°C for 5h, and taking out the sample; the amount of acrylic acid, potassium persulfate and glycerol is 10%, 0.4% and 1% of the total weight of the two solutions respectively; Step 3, soaking the hydrogel sample in deionized water for 24 hours to remove uncross-linked acrylic acid or polymer on the surface of the hydrogel; Step 4: sterilize the hydrogel under ultraviolet light for more than 30 minutes after demolding, and store it in a sealed container for future use.
[0040] Example 7 A method for preparing a nano marine traditional Chinese medicine composite dressing comprises the following steps: Step 1, dissolving 1% sodium alginate in water, adding 1% nano-cuttlebone, and adding 0.1% calcium citrate to react with the sodium alginate with calcium ions to obtain a solution; Step 2, adding the above solution to a 12wt% PVA aqueous solution, and adding monomer acrylic acid, adding a certain amount of initiator potassium persulfate and cross-linking agent glycerol, heating in a water bath at 85°C for 5h, and taking out the sample; the amount of acrylic acid, potassium persulfate and glycerol is 10%, 0.4% and 1% of the total weight of the two solutions respectively; Step 3, soaking the hydrogel sample in deionized water for 24 hours to remove uncross-linked acrylic acid or polymer on the surface of the hydrogel; Step 4: sterilize the hydrogel under ultraviolet light for more than 30 minutes after demolding, and store it in a sealed container for future use.
[0041] Example 8 A method for preparing a nano marine traditional Chinese medicine composite dressing comprises the following steps: Step 1, dissolving 1% sodium alginate in water, adding 1% nano-cuttlebone, and adding 0.1% calcium citrate to react with the sodium alginate with calcium ions to obtain a solution; Step 2, adding the above solution to a 14wt% PVA aqueous solution, adding an appropriate amount of monomer acrylic acid, adding a certain amount of initiator potassium persulfate and cross-linking agent glycerol, heating in a water bath at 85°C for 5h, and taking out the sample; the amount of acrylic acid, potassium persulfate and glycerol is 10%, 0.4% and 1% of the total weight of the two solutions respectively; Step 3, soaking the hydrogel sample in deionized water for 24 hours to remove uncross-linked acrylic acid or polymer on the surface of the hydrogel; Step 4: sterilize the hydrogel under ultraviolet light for more than 30 minutes after demolding, and store it in a sealed container for future use.
[0042] Example 9 A method for preparing a nano marine traditional Chinese medicine composite dressing comprises the following steps: The only difference between this embodiment and embodiment 4 is that in step 1, the amount of nano-cuttlebone is 2%.
[0043] Example 10 A method for preparing a nano marine traditional Chinese medicine composite dressing comprises the following steps: The only difference between this embodiment and embodiment 4 is that in step 1, the amount of nano-cuttlebone is 3%.
[0044] Example 11 A method for preparing a nano marine traditional Chinese medicine composite dressing comprises the following steps: The only difference between this embodiment and embodiment 5 is that in step 1, the amount of nano-cuttlebone is 2%.
[0045] Example 12 A method for preparing a nano marine traditional Chinese medicine composite dressing comprises the following steps: The only difference between this embodiment and embodiment 5 is that in step 1, the amount of nano-cuttlebone is 3%.
[0046] Example 13 A method for preparing a nano marine traditional Chinese medicine composite dressing comprises the following steps: The only difference between this embodiment and embodiment 6 is that in step 1, the amount of nano-cuttlebone is 2%.
[0047] Example 14 A method for preparing a nano marine traditional Chinese medicine composite dressing comprises the following steps: The only difference between this embodiment and embodiment 6 is that in step 1, the amount of nano-cuttlebone is 3%.
[0048] Example 15 A method for preparing a nano marine traditional Chinese medicine composite dressing comprises the following steps: The only difference between this embodiment and embodiment 7 is that in step 1, the amount of cuttlebone is 2%.
[0049] Example 16 A method for preparing a nano marine traditional Chinese medicine composite dressing comprises the following steps: The only difference between this embodiment and embodiment 7 is that in step 1, the amount of cuttlebone is 3%.
[0050] Example 17 A method for preparing a nano marine traditional Chinese medicine composite dressing comprises the following steps: The only difference between this embodiment and embodiment 8 is that in step 1, the amount of cuttlebone is 2%.
[0051] Example 18 A method for preparing a nano marine traditional Chinese medicine composite dressing comprises the following steps: The only difference between this embodiment and embodiment 8 is that in step 1, the amount of cuttlebone is 3%.
[0052] Comparative Example 1 According to a cuttlebone electrospun nanofiber hemostatic dressing capable of quickly stopping bleeding and a preparation method thereof disclosed in Chinese patent (CN202211068097.0), the commercially available cuttlebone was initially crushed with a high-speed grinder, and then the cuttlebone coarse powder was deproteinized and decolorized, and the dried cuttlebone powder was ground with an agate mortar to a particle size of 3 to 8 microns.
[0053] Comparative Example 2 Step 1, dissolve 1% sodium alginate in water, add 0.1% calcium citrate to react with sodium alginate by calcium ion crosslinking to obtain a solution; Step 2, add the above solution to a 6% PVA aqueous solution, and add 10% monomer acrylic acid, 0.4% initiator potassium persulfate and 1% crosslinking agent propylene glycol, heat in a water bath at 85°C for 5 hours, and take out the sample; Step 3, soak the above hydrogel sample in deionized water for 24 hours to remove the uncrosslinked acrylic acid or polymer on the surface of the hydrogel; Step 4, sterilize the hydrogel under ultraviolet light for more than 30 minutes after demolding, and seal and store for later use.
[0054] Comparative Example 3 The difference between this comparative example and comparative example 2 is only that: in step 2, the polyvinyl alcohol is 8%.
[0055] Comparative Example 4 The difference between this comparative example and comparative example 2 is that in step 2, the polyvinyl alcohol is 10%.
[0056] Comparative Example 5 The difference between this comparative example and comparative example 2 is that in step 2, the polyvinyl alcohol is 12%.
[0057] Comparative Example 6 The difference between this comparative example and comparative example 2 is that in step 2, the polyvinyl alcohol is 14%.
[0058] The dressing obtained by the above implementation method was tested: The particle size and morphology of Examples 1-3 and Comparative Example 1 are shown in Figure 2 As shown, it can be seen that the cuttlebone reaches the nanoscale after ultrasonic sand grinding. The surface of the 3-8 micron cuttlebone is relatively smooth and flat, while the nano cuttlebone can be seen as small spherical particles.
[0059] The antibacterial properties of Examples 1-3 and Comparative Example 1 are as follows: Figure 3 As shown, it can be seen that both 3-8 micron and nano-cuttlebone hydrogels have antibacterial ability, and the inhibitory effect of nano-cuttlebone hydrogel on Staphylococcus aureus is better than that of 3-8 micron cuttlebone.
[0060] The cytotoxicity of Examples 1-3 and Comparative Example 1 is as follows Figure 4 As shown, it can be seen that the cytotoxicity of nano-cuttlebone hydrogel and 3-8 micron cuttlebone hydrogel are both level 0, with good biocompatibility, and nano-cuttlebone hydrogel can promote cell proliferation.
[0061] The scanning electron microscope images of Examples 4-8 and Comparative Example 2 are as follows: Figure 5 As shown, through scanning electron microscopy observation of Example 5 and Comparative Example 3, it can be seen from the comparison between the two that the upper side polyvinyl alcohol / sodium alginate hydrogel is relatively smooth, and the lower side nano-cuttlebone hydrogel is rougher, which is beneficial to the transportation of oxygen and nutrients. This rough structure is formed by the attachment of the cuttlebone to the porous skeleton through hydrogen bonds and ionic bonds after the cuttlebone is added to the polyvinyl alcohol / sodium alginate hydrogel.
[0062] The mechanical properties of the hydrogels obtained in Examples 4-18 of the present invention and Comparative Examples 2-6 are as follows: Figure 6 As shown in Figure a, it can be seen that the hydrogel has good tensile properties, and after adding nano-cuttlebone, most of its properties are enhanced, and most of the tensile strengths reach 100kPa; the elongation at break increases with the increase of PVA content, reaching more than 100%, with good elasticity, which can meet the mechanical properties of wound dressings.
[0063] The swelling ratios of Examples 4-8 of the present invention are as follows: Figure 7 As shown in Figure a, the swelling properties of the hydrogel changed significantly before 7 hours, and the swelling tended to saturation after 24 hours. As the content of polyvinyl alcohol increased, the swelling slowed down and the water content decreased. Figure b shows the water content of each hydrogel at 48 hours. It can be found that with the increase of PVA content, the water absorption capacity of the hydrogel decreased.
[0064] The liver hemostasis model of the nano-cuttlebone hydrogel obtained in Example 5 of the present invention is as follows Figure 8 As shown in the figure, the hemostatic ability of nano-cuttlebone hydrogel was tested by the mouse liver hemostasis model. The mouse liver was pierced with an 18-gauge needle, and then photos were taken at 10s, 30s, and 60s to observe the hemostasis of the mouse. As can be seen from the figure, the hemostasis rate of nano-cuttlebone hydrogel is much higher than that of the blank group, and there is no obvious blood flow. Therefore, the nano-cuttlebone hydrogel dressing can achieve hemostasis in 1 minute.
[0065] The animal model of nano-cuttlebone hydrogel obtained in Example 5 of the present invention is as follows Fig. 9 As shown in the figure, firstly, a full-thickness wound model of rats was constructed to evaluate the wound healing ability. A wound with a diameter of about 1 cm was surgically cut on the back of the mouse, and the wound surface was covered with a nano-cuttlebone hydrogel dressing. It can be seen from the figure that the wound closure rate of the nano-cuttlebone hydrogel was much higher than that of the blank group. Therefore, the nano-cuttlebone hydrogel dressing can significantly accelerate the healing of the wound.
[0066] It can be seen from the above that the nano marine traditional Chinese medicine composite dressing of the present invention can provide a certain moist environment for the wound, so that the wound healing effect of the cuttlebone is significant, thereby promoting the rapid healing of the wound.
[0067] The above implementation cases only describe several specific implementation schemes of the present invention, rather than limiting the scope of the patent of the present invention. It should be noted that for ordinary technicians in this field, different improvements can be made to obtain other implementation schemes without creative work, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A method for preparing a nano marine Chinese medicine composite dressing, characterized in that: The following steps are involved: Step 1, grinding the cuttlebone and sieving to obtain cuttlebone powder; then performing ultrasonic grinding to a particle size of 1nm-200nm to obtain nano-cuttlebone, and drying and sterilizing; Step 2, dissolving a certain amount of sodium alginate, adding a certain amount of nano-cuttlebone obtained in step 1 and calcium citrate, so that the carboxyl group in the sodium alginate and the calcium ion are cross-linked to obtain a nano-cuttlebone solution; adding the obtained nano-cuttlebone solution to a hydrophilic polymer solution, and adding a certain amount of acrylic acid, potassium persulfate and glycerol, heating in a water bath at 80-90° C. for 4-6 hours to obtain a hydrogel sample; Step 3, soaking the obtained hydrogel sample in water for 20-30 hours to remove the acrylic acid or hydrophilic polymer that is not cross-linked on the surface.
2. The preparation method according to claim 1, characterized in that: In step 1, the cuttlebone is a decoction piece, which is ground and passed through an 80-mesh sieve; the drying is air drying or freeze drying, wherein the air drying temperature is 55-65° C.; the sterilization is ultraviolet sterilization, and the sterilization time is 0.5-2 h.
3. The preparation method according to claim 1, characterized in that: Step 1 The ultrasonic sand milling process is wet grinding, the medium is water, and the ratio of cuttlebone powder to water is 1: (10-20); zirconium beads are added in the ultrasonic sand milling process, the amount is 80-90wt% of the cuttlebone powder, and the diameter of the zirconium beads is 0.3-0.4mm; circulating condensed water is used in the ultrasonic sand milling process and controlled below 8°C.
4. The preparation method according to claim 1, characterized in that: Step 1: Add 0.3 wt% of sodium hexametaphosphate to the cuttlebone powder during the ultrasonic sand milling process.
5. The preparation method according to claim 1, characterized in that: The hydrophilic polymer in step 2 is at least one of polyvinyl alcohol, polyethylene glycol and gelatin, and the mass concentration of the hydrophilic polymer solution is 6-14%.
6. The preparation method according to claim 1, characterized in that: The mass concentrations of sodium alginate, nano-cuttlebone and calcium citrate used in the nano-cuttlebone solution in step 2 are 1-2%, 1-3% and 0.1-0.2%, respectively.
7. The preparation method according to claim 1, characterized in that: The volume ratio of the nano-cuttlebone solution to the hydrophilic polymer solution in step 2 is 1:0.8-1.
2.
8. The preparation method according to claim 1, characterized in that: The amounts of acrylic acid, potassium persulfate and glycerol used in step 2 are 6-14%, 0.25-0.6% and 0.6-1.4% of the total weight of the two solutions, respectively.
9. The nano marine traditional Chinese medicine composite dressing obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the nano marine traditional Chinese medicine composite dressing according to claim 9 in the preparation of drugs for rapid hemostasis and wound repair.
Citation Information
Patent Citations
Cuttlebone hemostatic dressing
CN115501375A
Hemostatic hydrogel as well as preparation method and application thereof
CN115887745A
Polysaccharide coating liquid as well as preparation method and application thereof
CN117918415A